One-year Mortality in COPD After an Exacerbation: The Effect of Physical Activity Changes During the Event. (1st November 2016) - Esteban, Cristóbal; Garcia-Gutierrez, Susana; Legarreta, Maria J.; Anton-Ladislao, Ane; Gonzalez, Nerea; Lafuente, Iratxe; Fernandez de Larrea, Nerea; Vidal, Silvia; Bare, Marisa; Quintana, José M.; -COPD group, IRYSS
ABSTRACT: Mortality is one of the most important outcomes in patients with chronic obstructive pulmonary disease (COPD). Different predictors have been associated with mortality, including the patient's level of physical activity (PA). The objective of this work was to establish the relationship between changes in PA during a moderate-to-severe COPD exacerbation (eCOPD) and 1-year mortality after the index event. This was a prospective observational cohort study with recruitment of 2, 484 patients with an eCOPD attending the emergency department (ED) of 16 participating hospitals. Variables recorded included clinical and sociodemographic data from medical records, dyspnea, health-related quality of life, and PA before the index eCOPD and 2 months after the hospital or ED discharge, as reported by the patient. In the multivariate analysis worsening changes in PA from baseline to 2 months after the ED index visit [odds ratio (ORs) from 2.78 to 6.31] was related to 1-year mortality, using the age-adjusted Charlson comorbidity index (OR: 1.22), and previous use of long-term domiciliary oxygen therapy or non-invasive mechanical ventilation at home (OR: 1.68). The same variables were also predictive in the validation sample. Areas under the receiver operating characteristic curve in the derivation and validation sample were 0.79 and 0.78, respectively. In conclusion, PA is the strongest predictor of dying in the following year, i.e., those with worsened PA from baseline to 2 months after an eCOPD or with very low PA levels have a higher risk.